Crowdfunding dynamics in the Philippines: An actor network theory approach - Doce, Lumer Jude P. (Animo Repository, 2022)
Crowdfunding is a fast-growing technology-enabled process that offers an alternative way of funding creative and innovative projects through an open call over the internet. In the domain of digital economy, this crowd-based platform affords a generative capability to produce promising solutions to funding challenges from a large pool of heterogeneous participants. Despite its generativity, the uptake of crowdfunding is low, leaving its economic potential to be unexplored in the Philippine setting. Recent literature establishes a strong foothold of campaign characteristics stemming from platform data. However, a seeming lack of attention to how its wider adoption may help deepen its appreciation within a particular ecological context is deemed a fertile ground for investigation. As well, a socio-technical angle holds a promising key of providing a more nuanced understanding of this financial technology. This research aims to analyze the dynamics of crowdfunding adoption among segments of Filipino Micro, Small and Medium Enterprises (MSMEs), as founders, using actor-network theory (ANT). ANT’S moments of translation were empirically grounded to multi-case sites in a qualitative research paradigm with reflexive thematic data analysis approach. The technological readiness characteristic derived from the founders was identified, the themes representing the conditions that help facilitate their crowdfunding process were discussed, and how these conditions influenced their crowdfunding experience was presented. This study concludes by discussing the contributions of the study to theory and practice, and guidance to future scholarly inquiry to the crowdfunding domain. Keywords: crowdfunding, technology adoption, actor network theory